Usefulness of Intravitreal dexamethasone implant in treatment of persistent cystoid macular edema due to Irvine-Gass syndrome - Mya Thida Ohn; Thompson E; Waghmare A; Chandra A; Karia N (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2019)
Introduction: Pseudophakic cystoid macular edema (CME) is one of the commonest causes of visual impairment after uneventful cataract surgery. There is no standardized protocol for pseudophakic CME and cases with refractory or persistent CME remained therapeutic challenge.  Purpose: To investigate outcomes of intravitreal dexamethasone implant for the treatment of pseudophakic cystoid macular edema (CME) not responding to topical therapy or periocular steroids. Method: Retrospective, single-practice data analysis from an electronic medical record system of 30 eyes (30 patients) with persistent pseudophakic CME receiving intravitreal dexamethasone implants were studied. Patients with history of uveitis, diabetes, previous intraocular surgery, complicated cataract surgery, retinal vascular diseases and macular telangiectasia (MACTEL) were excluded. Full demographic information including age, gender was entered. The cystoid macular edema (CME) was assessed by clinical examination and optical coherence tomography (OCT) scan.  Results: Mean age was 73.70 years ranged from 54 to 85 with 40% male and 60%female. All cases had routine phacoemulsification-IOL and received at least 4 weeks treatment with topical steroid with or without topical NSAIDs after been diagnosed with Irvine-Gass syndrome. Mean duration of CME before receiving the first implant was 22.87 weeks. 13.33% also had history of periocular steroid therapy.  Mean best corrected visual acuity (BCVA) improved from 57.4 ETDRS letters to 68.23 ETDRS letters on week 4-8 and 67.87 letters on week 52. Mean central subfield thickness (CST) at fovea improved from 469.67um to 269um on week 52. 46.67% had complete resolution of CME after the first implant and patients were able to be discharged on weeks 52. 53.33% had refractory CME within six months after the dexamethasone implant. Re-treatment was given when visual acuity reduced to 6/12 or worse. Out of 30 cases, 26.67% required two implants and 10% required three on week 52.  Conclusion: This study concluded that intravitreal dexamethasone implant is useful and safe as a therapy of persistent pseudophakic CME. Elevated intraocular pressure was found in 13.33% and only half of those required topical antiglaucoma therapy.